2018
DOI: 10.18632/oncotarget.25978
|View full text |Cite
|
Sign up to set email alerts
|

Coriolus versicolor biomass increases dendritic arborization of newly-generated neurons in mouse hippocampal dentate gyrus

Abstract: Brain cognitive reserve refers to the ability of the brain to manage different challenges that arise throughout life, making it resilient to neuropathology. Hippocampal adult neurogenesis has been considered to be a relevant contributor for brain cognitive reserve and brain plasticity. Coriolus versicolor (CV), a common healthful mushroom, has been receiving increasing attention by its antitumoral, anti-inflammatory, antioxidant, antibacterial, and immunomodulatory properties, including in the hippocampus. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Interestingly, a study reported the benefit effect of O 3 on Menière’s disease ( Pawlak-Osinska et al, 2004 ). Moreover, as reported for polyphenols and mushrooms ( Hsiao et al, 2016 , Ferreiro et al, 2018 , Oh et al, 2014 , Pan et al, 2018 , Hasanzadeh et al, 2020 , Wang et al, 2019b ), O 3 has been found to be involved in β-catenin system ( Emon et al, 2017 ) as well as in NLRP3 (nitrogen permease regulator-like 3) inflammasome ( Yu et al, 2017 , Wang et al, 2018c ).…”
Section: Molecular Mechanisms Involving Ozone (O 3 mentioning
confidence: 62%
See 1 more Smart Citation
“…Interestingly, a study reported the benefit effect of O 3 on Menière’s disease ( Pawlak-Osinska et al, 2004 ). Moreover, as reported for polyphenols and mushrooms ( Hsiao et al, 2016 , Ferreiro et al, 2018 , Oh et al, 2014 , Pan et al, 2018 , Hasanzadeh et al, 2020 , Wang et al, 2019b ), O 3 has been found to be involved in β-catenin system ( Emon et al, 2017 ) as well as in NLRP3 (nitrogen permease regulator-like 3) inflammasome ( Yu et al, 2017 , Wang et al, 2018c ).…”
Section: Molecular Mechanisms Involving Ozone (O 3 mentioning
confidence: 62%
“…Preconditioning is a process whereby an initial low dose of a stressor agent upregulates adaptive mechanisms that enhance resilience against subsequent and acute stressor agents within a time-sensitive window of ∼ 10–14 days ( Calabrese, 2016 ). Different studies demonstrated that the supplementation with Coriolus versicolor ( Ferreiro et al, 2018 , Scuto et al, 2019 , Trovato Salinaro et al, 2018 , Trovato et al, 2016a ), and Hericium Herinaceus ( Trovato Salinaro et al, 2018 , Trovato et al, 2016b ) biomass and polyphenols ( Mao et al, 2019 ) can maintain the response to neutralize intracellular pro-oxidant/neuroinflammatory status, preventing different neurological conditions.…”
Section: Effect Of Ozone Oxidative Preconditioning On Oxidative Stresmentioning
confidence: 99%
“…In addition, genetically susceptible individuals with impaired mucosal integrity, undergo escaping of microbial antigens through the epithelial barrier, presenting higher risk for inappropriate immune response and/or underlying chronic inflammation [60]. Our results are relevant to the biology of chronic inflammatory pathology, both in central and peripheral tissues, as many researches have demonstrated that polysaccharides, naturally occurring substances derived from plants or mushrooms [23,37], exhibit favorable therapeutic and health-promoting benefits [61], particularly in relation to diseases associated with inflammation [22,[37][38][39]. HE is a medicinal fungus, with the effect of prevention and treatment of gastrointestinal disorders, particularly, owing to its potential therapeutic effect on cancer, promoting immune stimulation and improving lipid metabolism and thus gastrointestinal pathology, where it has been shown that HE supplementation can improve the immune system via regulation of metabolism and composition of gut microbiota [60], thereby reducing ulceration and providing protection against gastric mucosal damage [62].…”
Section: Discussionmentioning
confidence: 68%
“…Notably, as previously mentioned, several studies have demonstrated significant ultrastructural reductions in dendritic innervation densities, at level of cochlear ganglion neurons, pointing the possibility that neurotoxicity plays an important role in the pathology of MD [6]. Interestingly, a recent study in mice has found that Coriolus versicolor biomass promotes significant increases in dendritic length and branching and total dendritic volume of immature neurons, suggesting a positive effect of oral Coriolus versicolor administration on hippocampal neurogenic reserve [74]. Taking all this into account and given the inflammatory pathogenesis of MD degenerative damage, our findings of reduction in oxidative stress and inflammatory mediators associated with increased anti-inflammatory metabolites in mushroom-treated patients has innovative therapeutic potential.…”
Section: Discussionmentioning
confidence: 76%